Political risk effect on financial market returns; between magnification and neglection: Evidence from Egyptian stock market - Alaaeldin, Salma Mohamed (AUC Knowledge Fountain, 2018)
There is extensive debate on whether political risk is an important factor that influences financial markets and investment decision, especially in developing economies. The main aim of this thesis is to analyze the effect of political risk on stock market returns while controlling for financial risk, economic risk, interest rates and foreign exchange rates. The main methodology involves estimating the model using a regime switching model to account for changes in volatility. The sample period starts from January 2007 to August 2017. The data includes: EGX30 returns over the period, Political risk as proxied by International Country Risk Guide (ICRG) political risk index, economic risk as proxied by International Country Risk Guide (ICRG) economic risk index, financial risk as proxied by International Country Risk Guide (ICRG) financial risk index, Interest rate corridor rate offered by central bank and the Exchange rate between Egyptian pound and US Dollar. The results of the thesis show that political risk proves to be a significant driver for the market returns during high volatility regimes that reflects an unrest in the market, while its impact disappear during stable times.